PENGEMBANGAN MODEL LOYALITAS NASABAH PADA PERBANKAN SYARIAH (BANK SYARIAH MANDIRI) - Anita Ilmaniati; Iwan Inrawan Wiratmadja (Badan Penerbit Jurnal, Faculty of Engineering, Universitas Brawijaya, 2016)
Customer loyalty is the key to customer retention, so that customer loyalty needs to be accomplished before reaching customer retention. Customer satisfaction is considered as an important factor and a positive effect on customer loyalty so far. Several previous studies have revealed that, besides customer satisfaction, there are other factors that determine customer loyalty. Until now, research on other factors that determine the customer loyalty give varies results. This research will develop a model of customer loyalty in the Islamic banking institutions, especially the Bank Syariah Mandiri (BSM) where data trends of satisfaction and customers loyalty is not proportional, by using the PLS-SEM in data processing. The aim of this study was to develop a model of customer loyalty in banking institutions, especially the Islamic banking (Bank Syariah Mandiri). The results showed that customer satisfaction is not significantly affect customer loyalty, and only the quality of services that significantly affect customer loyalty. Switching barrier and customer trust is also proven not affect customer retention both on the main effects and on the interaction effects with customer satisfaction. The result is expected to be a managerial reference to increase customer loyalty.